2022
DOI: 10.2147/ccid.s393290
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Psychotherapeutic Approaches to the Treatment of Eczema

Abstract: Introduction Patients with eczema suffer from high psychological burden, often caused and exacerbated by chronic pruritus, which leads to a vicious itch-scratch cycle. Although much of the literature focuses on treating the physiological factors that lead to pruritus, little attention has been given to the cognitive, behavioral, and social factors associated with the itch-scratch cycle. We conducted a literature review to investigate whether treatments aimed at psychosocial factors could be effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The interventions explored in these studies majorly centered on financial incentives, which were often paired with other behavioral economic concepts such as framing, social influences, reinforcement, and feedback. While the interventions showcased promising results, the effectiveness varied, indicating a complex interplay of factors influencing medication adherence [6]. The review identified a total of thirty-four relevant studies, with a predominant focus on chronic conditions including diabetes mellitus, human immunodeficiency virus (HIV), and cardiovascular and renal diseases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The interventions explored in these studies majorly centered on financial incentives, which were often paired with other behavioral economic concepts such as framing, social influences, reinforcement, and feedback. While the interventions showcased promising results, the effectiveness varied, indicating a complex interplay of factors influencing medication adherence [6]. The review identified a total of thirty-four relevant studies, with a predominant focus on chronic conditions including diabetes mellitus, human immunodeficiency virus (HIV), and cardiovascular and renal diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the implications of these findings in the context of eczema management, Nurchis et al's study underscores the potential of nudging interventions as potent tools for shaping positive behaviors among individuals affected by eczema [6]. Given the established role of alcohol and tobacco consumption as triggers for eczema flare-ups, the integration of successful nudging strategies holds promise as a cornerstone in comprehensive eczema care frameworks.…”
Section: Nudging Interventions On Alcohol and Tobacco Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been suggested that itch cognitive distortion from prefrontal cortex disturbance may be associated with some neuropsychiatric symptoms 29 . Hence, therapeutic interventions to reduce stress may be beneficial for reducing pruritus and skin lesions in AD, as well as related psychological symptoms 31,32 …”
Section: The Influence Of Psychological State In Dermatological Condi...mentioning
confidence: 99%
“…29 Hence, therapeutic interventions to reduce stress may be beneficial for reducing pruritus and skin lesions in AD, as well as related psychological symptoms. 31,32 The role of psychosocial factors, such as psychosocial stress or negative expectations, might also be relevant in "sensitive skin", characterised by unpleasant symptoms (e.g., stinging, burning, pain, pruritus, tightness and tingling sensations) but no objective clinical features, where changes in the cutaneous free nerve endings could play a role. 33,34 Elucidation of the pathophysiological mechanisms and the interaction between the central nervous system and the skin underlying these psychocutaneous disorders is required to help understand the interactions between mental state, dermatoses, and skin symptoms to find the most suitable holistic therapies to improve patients' well-being and QoL.…”
Section: The Influence Of Psychological State In Dermatological Condi...mentioning
confidence: 99%